EPHX1 and ERCC2 polymorphisms are associated with cisplatin-induced nephrotoxicity and prognosis in Thai cancer patients - Saad Ahmed; Jakris Eu-ahsunthornwattana; Thanaporn Thamrongjirapat; Aruchalean Taweewongsounton; Yutthana Rittavee; Nintita Sripaiboonkit Thokanit; Montien Ngodngamthaweesuk; Pitichote Hiranyatheb; Thanyanan Reungwetwattana; Nuttapong Ngamphaiboon; Natini Jinawath (PLoS ONE, 2025)
Cisplatin is a widely used chemotherapeutic drug for various cancers. One of the common adverse effects of cisplatin is nephrotoxicity including acute kidney injury (AKI) and acute kidney disease (AKD). Single Nucleotide Polymorphisms (SNPs) can be used to identify cancer patients who are susceptible to developing cisplatin-induced nephrotoxicity (CIN). In this study, we validated the association between 6 SNPs in the drug metabolizing enzyme genes, SLC22A2 (rs316019) & EPHX1 (rs1051740), and the DNA repair genes, ERCC1 (rs11615 & rs3212986) & ERCC2 (rs13181 & rs1799793), and CIN in the 169 Thai patients with head and neck, lung, or esophageal cancer. Effect of these SNPs on cumulative incidence of AKD, progression-free survival (PFS), and overall survival (OS) was also assessed. EPHX1 rs1051740 TC genotype was significantly associated with AKD in co-dominant [OR 2.894, 95% CI 1.091–7.680; P = 0.033] and over-dominant [OR 2.793, 95% CI 1.333–5.851; P = 0.006] models, and with an increased cumulative incidence of AKD (P = 0.021). Additionally, ERCC2 rs13181 and rs1799793 were significantly associated with OS (P = 0.002 and 0.004). Our results reveal an association between EPHX1 rs1051740 and AKD, and confirms the previously reported associations between ERCC2 SNPs and OS. These findings may help in predicting CIN in Thai cancer patients.